Perianal Rhabdomyosarcoma: Report of a Case in an Infant and Review of the Literature. Issue 1 (22nd February 2012) - Gökdemir, Gonca; Ekmen, Sevgi; Gungor, Sule; Singer, Ralfi
<x xml:space="preserve">Abstract</x> Abstract: Rhabdomyosarcoma of the perianal and perineal region is a rare sarcoma of childhood with a poor prognosis. The clinical findings are similar to those of condyloma accuminata, which makes it difficult to diagnose. There are a few reports of this disease in the dermatologic literature. We present a 15‐month‐old girl with a polypoid anal mass diagnosed as embryonal rhabdomyosarcoma and a review of the current literature.